How Does Social Media Platforms Help to Improve Business Performances during the COVID-19 Pandemic? A Study of TikTok - Rajesh Kumar Nair; Hareeprriya A/P Sugumaran; Daisy Mui Hung Kee; Siew Wvy Heng; Hilari Mei; Chumengyao Huang; Vrutika Doshi; Varsha Ganatra (Journal of The Community Development in Asia, 2022)
The study investigates to which extent social media platforms, specifically TikTok, have driven users’ satisfaction and lead to business performance improvements. Entrepreneurs, such as small business owners, agents, and drop shippers were facing tremendous challenges to carry out their businesses during the COVID-19 pandemic. The existence of social media applications has allowed them to promote their products or services in various forms despite the failure to conduct businesses physically. However, they tend to use certain social media application only if it satisfies their business needs. This study employs 100 samples of data from students in Universiti Sains Malaysia collected through an online questionnaire. Subsequently, SPSS analysis was conducted and generated descriptive, Pearson correlation, and regression analysis to support the hypotheses. The findings of this study revealed that users’ satisfaction towards social media, specifically TikTok, have led to customer engagement, personal branding, and effective promotion. Thus, entrepreneurs shall first adopt social media application that provides the highest level of satisfaction to motivate continuous usage of the application which then gradually improves their business performance.